Initiating Superior Madrasah Through Madrasah Curriculum Planning in the Era of Society 5.0 - Sugiarto, Danu; Fitri, Agus Zaenul (IJECA (International Journal of Education and Curriculum Application), 2023)
Islamic educational institutions have new challenges in facing the era of society 5.0. Islamic educational institutions must deliver graduates who are capable of mastering technological developments while upholding good morals as the core values of madrasas. This study aims to find out how madrasas are able to become superior madrasas through madrasah curriculum planning in the era of society 5.0 in order to build the khaira ummah generation. This type of research is literature study using a descriptive approach. Research data collection was carried out using documentation techniques, namely by collecting data sources from various literature in the form of books, journals, proceedings, and valid scientific papers. Data analysis used qualitative analysis in the form of data reduction, data presentation, and conclusions. The results of the analysis show that becoming a superior madrasah in the era of society 5.0 is carried out by emphasizing the quality of curriculum planning which includes objectives, content, and learning methods to be used. It is hoped that this research can be an illustration for madrasas in determining the content and learning methods of the curriculum so that they are able to produce graduates who are competent in intellect and polite in behavior.